When general practitioners meet new evidence: an exploratory ethnographic study - Ole Olsen (Taylor & Francis Group, 2017)
Objective: To explore how general practitioners (GPs) think and act when presented with new evidence in relation to planned home birth and a proposal to change information practices. Design: Exploratory ethnographic study of GPs. The GPs were encountered one or more times during a two-year period, 2011-2013, while the author tried to set up formal focus group interviews. Dialogues about the evidence, personal experiences, values and other issues unavoidably occurred. Field notes were written concomitantly. Setting: Danish GPs, primarily in Copenhagen. Subjects: Fifty Danish GPs. Results: The GPs reacted very differently, both spontaneously and later. Spontaneous reactions were often emotional involving private and professional experiences whereas later reactions were more influenced by rational deliberations. Approximately half the GPs (n = 18) who were asked whether they would personally hand out the local information leaflet about home birth were prepared to do so. The time lag between presentation of the evidence and the GPs' decision to hand out the leaflets was up to one and a half year. Conclusions: A significant number of GPs were prepared to change their information practices. However, for many GPs, the new evidence challenged previous perceptions, and ample time and resources for dialogue, deliberations and adaptation to local circumstances were required to accommodate change. Implications: Changing information practices on a larger scale will require a systematic approach involving key stakeholders.Key Points Current awareness•Patients and pregnant women should receive evidence-based information about possible choices of care - also in relation to place of birth. Most important results•Doctors often find the new evidence supporting planned home birth counterintuitive and spontaneously react emotionally rather than rationally to the evidence.•The new evidence challenging previous views elicits fast, emotional reactions, later deliberate reflections, perhaps cognitive dissonance and, finally, for some, change in clinical practice. Significance for the readers•The findings may be applicable to other fields where an evidence-based choice between an interventionist and a conservative approach is relevant.